Imaging genetics of FOXP2 in dyslexia - Wilcke, Arndt; Ligges, Carolin; Burkhardt, Jana; Alexander, Michael; Wolf, Christiane; Quente, Elfi; Ahnert, Peter; Hoffmann, Per; Becker, Albert; Müller-Myhsok, Bertram; Cichon, Sven; Boltze, Johannes; et al. (European journal of human genetics : EJHG, 2012)
Dyslexia is a developmental disorder characterised by extensive difficulties in the acquisition of reading or spelling. Genetic influence is estimated at 50-70%. However, the link between genetic variants and phenotypic deficits is largely unknown. Our aim was to investigate a role of genetic variants of FOXP2, a prominent speech and language gene, in dyslexia using imaging genetics. This technique combines functional magnetic resonance imaging (fMRI) and genetics to investigate relevance of genetic variants on brain activation. To our knowledge, this represents the first usage of fMRI-based imaging genetics in dyslexia. In an initial case/control study (n = 245) for prioritisation of FOXP2 polymorphisms for later use in imaging genetics, nine SNPs were selected. A non-synonymously coding mutation involved in verbal dyspraxia was also investigated. SNP rs12533005 showed nominally significant association with dyslexia (genotype GG odds ratio recessive model = 2.1 (95% confidence interval 1.1-3.9), P = 0.016). A correlated SNP was associated with altered expression of FOXP2 in vivo in human hippocampal tissue. Therefore, influence of the rs12533005-G risk variant on brain activity was studied. fMRI revealed a significant main effect for the factor ’genetic risk’ in a temporo-parietal area involved in phonological processing as well as a significant interaction effect between the factors ’disorder’ and ’genetic risk’ in activation of inferior frontal brain areas. Hence, our data may hint at a role of FOXP2 genetic variants in dyslexia-specific brain activation and demonstrate use of imaging genetics in dyslexia research. Dyslexia is a developmental disorder characterised by extensive difficulties in the acquisition of reading or spelling. Genetic influence is estimated at 50-70%. However, the link between genetic variants and phenotypic deficits is largely unknown. Our aim was to investigate a role of genetic variants of FOXP2, a prominent speech and language gene, in dyslexia using imaging genetics. This technique combines functional magnetic resonance imaging (fMRI) and genetics to investigate relevance of genetic variants on brain activation. To our knowledge, this represents the first usage of fMRI-based imaging genetics in dyslexia. In an initial case/control study (n = 245) for prioritisation of FOXP2 polymorphisms for later use in imaging genetics, nine SNPs were selected. A non-synonymously coding mutation involved in verbal dyspraxia was also investigated. SNP rs12533005 showed nominally significant association with dyslexia (genotype GG odds ratio recessive model = 2.1 (95% confidence interval 1.1-3.9), P = 0.016). A correlated SNP was associated with altered expression of FOXP2 in vivo in human hippocampal tissue. Therefore, influence of the rs12533005-G risk variant on brain activity was studied. fMRI revealed a significant main effect for the factor ’genetic risk’ in a temporo-parietal area involved in phonological processing as well as a significant interaction effect between the factors ’disorder’ and ’genetic risk’ in activation of inferior frontal brain areas. Hence, our data may hint at a role of FOXP2 genetic variants in dyslexia-specific brain activation and demonstrate use of imaging genetics in dyslexia research.